PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN INFRASTRUKTUR KAMPUNG TENGAH (STUDI ALOAKSI DANA DESA DI KAMPUNG TENGAH KECAMATAN MEMPURA KABUPATEN SIAK TAHUN 2016) - Yeni, Alfa; Tinov, M. Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Centralized develoment has led to disparities between urban and rural areas from different perspectives. One of the government’s strategies to establish to reduce disparities and make villages more autonomous and self-reliant is to allocate village funds which then involve all members of the community at every stage of the activities resulting from this policy.The pupose and research is to identify; 1. Know the infrastructure development in the middle village in 2016; 2. Analyze the factore that development in the middle village by 2016. The method used in this research is descriptive method with qualitative approach. Data type is primary data and secondary data. Data collection techiques in the study are interviews and documentation. Tachniqu and data analysis used is desciptive qualitative data analysis.Based on the result of the results of this study concluded that the particiption of the community in the development of the village is through the use of village funds, overall sosiety is still low public participation, this lavks the opportunity that is owned as a sciety to participate with the ability and willingness of the community is still not able to reach a higher stage.The village apparatus is being linked in the aducation of the village apparatus is considered minimal, the training and education only once in 2016.Keywords : Development, Community Participation, Villages Fund Allocation